Highland Sinner - Howell, Hannah (New York, NY Zebra Books, Kensington Publishing Corp., 2008)
Sir Tormand Murray is certainly a rogue, but a callous killer? Never. Yet he cannot explain how he came to wake up next to the butchered body of one of his former lovers. Someone is prepared to kill again and again until Tormand is found guilty and hanged. And his only hope of discovering the culprit lies with Morainn Ross, a reclusive, sensual beauty gifted with second sight. Branded a witch, Morainn has never met a man who accepted her strange talent, much less one who could so easily enflame her passion. There's no resisting Tormand's rugged masculinity and no escaping the enemy who grows more twisted every day. And even as logic decrees that a lasting union is impossible, Morainn knows her destiny is bound forever with the knight who has claimed her, body and soul.
Keywords: Fiction; Historical fiction; Love stories